Breast Imaging Fellowship Match: Applicants' Perspectives of Years Two and Three. Issue 5 (15th August 2020) - Lee, Michelle V; Katzen, Janine T; Al-Khalili, Rend; Choudhery, Sadia; Whitman, Gary; Brem, Rachel
Abstract: Objective: The purpose of this study is to summarize the results of a survey distributed by the Society of Breast Imaging (SBI) to assess applicants' experience with the 2018 and 2019 Breast Imaging Fellowship Match process. Methods: In this institutional review board–exempt study, the SBI issued an anonymous survey to all matched applicants in an attempt to gauge their experience with the 2018 and 2019 Match process. Results: The survey was sent to all 2018 and 2019 matched applicants and 105/236 (45%) responses were received. The majority (75%, 79/105) of respondents reported a positive experience with the Match, with at least a 4/5 rating, and only 3% (5/105) reported a rating below 3/5. There was some improvement in 2019, with 86% (24/28) of respondents reporting at least a 4/5 rating compared to 71% (55/77) in 2018. No respondent reported a score below a 3/5 rating in 2019. The most commonly cited issues with the Match were the timing of the Match process, the need for a universal application, and the burden of travel. Location and program reputation were the two most important factors contributing to the final rank order of programs. Conclusion: The great majority of applicants felt that the Match created a positive experience. Planned areas of improvement include the implementation of a universal application, the transition to virtual interviews, and a condensed timeline. These measures are likely to increase applicant satisfaction and provide a fair and efficient experience for future breast radiologists. Graphical Abstract: